How Supervisors Can Support Doctoral Students to Publish and Not Perish in Academia - James Marson; Katy Ferris (Encyclopedia, 2023)
“Publish or perish” is a term used for the culture adopted in universities, whereby academic members of staff, typically although not exclusively on research and teaching contracts, are required to publish research. Minimum levels of quantity and quality may apply and these may be included in key performance indicators and annual staff reviews to ensure compliance. Whilst this culture has been reported in universities for nearly a century, most recently it has cascaded down to doctoral students who are increasingly expected to publish and otherwise disseminate research during their studies (i.e., research outside of that which is to be submitted in their thesis). This entry relates primarily to doctoral students in a UK setting and studying a monograph route (rather than a published papers submission) in the humanities. It further explores the role played by supervisors to help doctoral students to publish, and in turn the help and guidance supervisors need to offer as support. Many of the findings explored in this entry apply equally beyond the parameters noted above, and, as demonstrated in the literature, international students and institutions are facing similar issues.